DEVELOPMENT OF SMART GOVERNANCE MEASUREMENT FRAMEWORK TO CREATE A SUSTAINABLE BANDUNG SMART CITY - Osni Erza; M. Suparmoko; Tulus T.H. Tambunan (PENANOMICS: International Journal of Economics, 2022)
This study aims to examine the development of a Smart Governance measurement framework to create a sustainable Bandung Smart City. The measurement of Smart Governance identifies the potential of Bandung city and analyzes what indicators play a major role in the dimensions of Smart Governance, as well as implying government policy as a bridge between the community and the government in making decisions. This research uses Mixed Method (Quantitative and Qualitative). The data were processed using SPSS 25 and LISREL 8.80 app, with Structural Equation Modeling (SEM), the testing based on Confirmatory Factor Analysis (CFA) theory, which is used to support quantitative data. For qualitative data, researchers conducted interviews with stakeholders who were directly involved in the development of Bandung Smart City. The Smart City variable from the Smart Governance Dimension has 4 Sub-dimensions which have standardizes factor loading which explains that all sub-dimensions are meaningful and significant to the Smart Governance Dimension namely Leadership Stakeholders: Mayor, Deputy Mayor, and OPD of (0.83) , Governance Transparency (0.97), Community participation in decision making (0.59), and Infrastructure (0.94). Where the value of CR (0.91), and AVE (0.72). For further research, it is recommended to examine a broader dimension of Smart City, which include Smart Economy, Smart People, Smart Mobility, Smart Environment, Smart Living, Smart Branding, Smart Energy, Smart Society, along with other stakeholders such as relevant government agencies, colleges, entrepreneurs, medical teams and others.